Gemini 1.5 Pro Performance Degradation on Qasper with Context Position Shifts - Assignee Research (Assignee Research, 2026)
This report synthesises findings from 1 peer-reviewed paper addressing the following research question: How does the performance of Gemini 1.5 Pro on the Qasper dataset degrade as the position of relevant information shifts from the beginning to the middle versus the end of a 500k token context window. 8 claims were extracted from source literature; 8 were independently verified against retrieved documents. An automated multi-reviewer quality assessment produced a score of 8.1/10. This report is
Machine-generated literature synthesis.